Predicting water retention curve and resilient modulus of compacted natural and recycled pavement unbound granular materials. Issue 13 (10th November 2021) - Han, Zhong; Zou, Wei-lie; Wang, Xie-qun
ABSTRACT: The water retention curve (WRC) and resilient modulus ( MR ) of pavement materials are essential for performing hydro-mechanical analysis on pavement structures. This paper introduces one model to predict the WRC and one model to predict the MR -moisture content relationships for compacted natural and recycled unbound granular materials (UGMs), which are typical construction materials for pavements' base and sub-base layers. The WRC model requires UGMs' gradation information and only one WRC measurement (preferably at optimum moisture content) for prediction. The predicted WRC can be further used in the MR model, along with measured MR at saturated and optimum moisture content conditions, to predict the influence of moisture content on the MR of UGMs. Both models require limited experimental data to enable predictions and do not need parameter calibration procedures, and thus are simple to apply. Reliability of the two models was examined using experimental data of 20 UGMs, including 10 natural and 10 recycled UGMs. It is demonstrated that both models achieved reasonable predictions for all UGMs used in this study.